SOCIAL EFFECTIVENESS OF BUSINESS ENTITIES - Perevozova, I.V.; Popadynets , I.R. (The actual problems of regional economy development, 2016)
The article is aimed at investigation of social effectiveness of business entities. Social aspect of business is becoming a necessary component of success, increase of profitability and competitiveness as well as minimization of risks. Social effectiveness is referred to as correspondence between economic activity and main social needs and aims of society, interests of the staff and interests of a certain person. Investigation of social effectiveness of business entities is suggested to analyze with the help of social factors. Social factors are characterized by variability of expectations, relations and interests of society, staff and individuals. We suggest generalized classification of factors which have an impact on social effectiveness of business, we single out external and internal factors. To external factors belong: income of the population, differentiation of population according to income, migration, level of salaries, level of legality of income of population, family status of population, employment rate, age structure of population etc. As for internal factors we single out the following: low level of basic professional training, use of unskilled workers, absence of conditions for creativity, imperfection of system of motivation of professional growth, absence of specialized centers for certification training etc. Quantity and quality analysis of the above mentioned factors will enable to determine the level of social effectiveness of business entities. For analyses of degree of influence of factors on effectiveness we worked out a questionnaire of expert assessment which is represented in the form of assessment scale. We conducted a questionnaire and analyzed expert results and determined degree of influence of factors on social effectiveness of business. Assessment of level of social effectiveness of business entities was carried out by expert method of certain factor and was represented by a formula. The scale of assessment of level of social effectiveness of business entities in percentage by separate factors: 100-90 – high level, 89-75 – middle level, 74-60 – satisfactory level, 39-40 – low level, 30-0 – absent level. In the article we calculated separately levels of social effectiveness of business entities for external and internal factors. We found out that both external and internal factors are on the middle level, between 79-85%. The given calculations demonstrate reserve for increase of social effectiveness of business entities. Main measures for increase of social effectiveness of business entities are logically united into the following groups: science and technology group; management and economic group; social and psychological group; foreign group. These provisions allow to minimize the social impact of reserve businesses, which, in turn, increase their efficiency and competitiveness, and reduce business risks. Thus growth of effectiveness reveals itself in maximization of social and economic effect and minimization of working hours. Social effect of business entities expresses itself in providing better conditions of life, preconditions are created for further development of the staff in general as well as individual. Mechanism of social effectiveness of business entities is the basis for development, transition from simple to complex needs, from materialistic to spiritual, from economic to political and thus to fully developed personality. Meanwhile higher needs should be considered as main wealth of the society, main factor of social and economic progress. Contradiction between endless growth of social and economic needs and limited resourses of additional time, which can be aimed at satisfaction of them at every certain period of time appears as a driving force of social and economic development. JEL: M 20